Food beliefs and practices in urban poor communities in Accra: implications for health interventions - Sandra Boatemaa; Delali Margaret Badasu; Ama de-Graft Aikins (BMC, 2018)
Abstract Background Poor communities in low and middle income countries are reported to experience a higher burden of chronic non-communicable diseases (NCDs) and nutrition-related NCDs. Interventions that build on lay perspectives of risk are recommended. The objective of this study was to examine lay understanding of healthy and unhealthy food practices, factors that influence food choices and the implications for developing population health interventions in three urban poor communities in Accra, Ghana. Methods Thirty lay adults were recruited and interviewed in two poor urban communities in Accra. The interviews were audio-taped, transcribed and analysed thematically. The analysis was guided by the socio-ecological model which focuses on the intrapersonal, interpersonal, community, structural and policy levels of social organisation. Results Food was perceived as an edible natural resource, and healthy in its raw state. A food item retained its natural, healthy properties or became unhealthy depending on how it was prepared (e.g. frying vs boiling) and consumed (e.g. early or late in the day). These food beliefs reflected broader social food norms in the community and incorporated ideas aligned with standard expert dietary guidelines. Healthy cooking was perceived as the ability to select good ingredients, use appropriate cooking methods, and maintain food hygiene. Healthy eating was defined in three ways: 1) eating the right meals; 2) eating the right quantity; and 3) eating at the right time. Factors that influenced food choice included finances, physical and psychological state, significant others and community resources. Conclusions The findings suggest that beliefs about healthy and unhealthy food practices are rooted in multi-level factors, including individual experience, family dynamics and community factors. The factors influencing food choices are also multilevel. The implications of the findings for the design and content of dietary and health interventions are discussed.